(untitled) (Global Journal of Management and Business Research, 2013)
In India more than 72% population is living in villages and FMCG companies are famous in selling their products to the middleclass households, it means rural India is a profitable and potential market for FMCG producers. Rural consumers’ incomes are rising and willing to buy the products which improve their lifestyle. Producers of FMCG have to craft their marketing strategies exclusively for rural consumers. In this process they need to understand the rural consumer buying behaviour which may differ geographically. The present study focuses on the understanding of rural consumer buying behavior for FMCG in Haryana. The study stresses on the factors which the purchasing of rural consumers. The study was conducted in four districts of Haryana namely panipat, jind, kuruksetra and gurgaon.